Role of Ultrasonography in Predicting Gastro-oesophageal Varices in Patients with Liver Cirrhosis - Gyawali, Merina; Acharya, Ramesh Raj (Journal of College of Medical Sciences-Nepal, 2021)
Introduction Upper Gastrointestinal endoscopy is considered the best screening tool in detecting gastroesophageal varices in patients with cirrhosis. Ultrasonography of the abdomen can be used for assessment of liver and portal system. This research was undertaken to demonstrate that the portal vein diameter and splenic size by ultrasonography can be used as a non-invasive predictor of gastro-esophageal varices. Methods A cross-sectional hospital based study comprising of 290 consecutive patients with liver cirrhosis were enrolled between November 2019 to November 2020. Clinical profile at admission and sonological splenic size and portal vein diameter were studied in all cirrhotic patients. Patients were classified into 2 groups: one with presence of varices and second without varices. Data entry was done in Statistical Packages for the Social Sciences version 20. Results The mean age of subjects was 52±13.26 years with a range of 27 – 82 years of age (M:F=2:1). The commonest etiology of cirrhosis was chronic alcohol consumption. The prevalence of varices in cirrhotics was 42.8%. Average portal vein diameter of patients without gastro-esophageal varices was 11.12 ± 1.36 mm, while it was 12.81 ± 1.62 mm in patients with varices (p < 0.001). Average spleen size in cirrhotics without varices was 12.44 ± 1.32 cm and with varices was 14.32 ± 2.42 cm. This difference was also statistically significant (p < 0.001). Conclusions Measurement of portal vein diameter and spleen size by ultrasonography can be recommended as a non invasive predictor for gastro-oesophageal varices in patients with liver cirrhosis . Keywords: cirrhosis; portal vein diameter; spleen size; ultrasonography; gastro-oesophageal varices